Enhancement effects of ethanolic extract of Fagonia cretica on Bisphenol A (BPA)-induced genotoxicity and biochemical changes in rats - Abd-El-Moneim, Omaima Mohamed (2021)
The results demonstrated that the treatment with BPA induced a significant elevation in genetic abnormalities and deleterious effects in biochemical parameters in relation to untreated control. FCE treatment was found to be significantly diminished the massive damage in the genetic constituents and dangerous alterations in biochemical parameters with respect to BPA treatment alone. These enhancements were increased by increasing the dose level of FCE. Moreover, better results were clarified by utilizing FCE as a protective agent than its utilization as a therapeutic agent especially by using the high dose (5.0 g/kg), in which mostly genetic and biochemical alterations were observed to be restored towards natural levels.